Synergistic effect of vegetation and air temperature changes on soil water content in alpine frost meadow soil in the permafrost region of Qinghai-Tibet - Wang, Genxu; Li, Yuanshou; Hu, Hongchang; Wang, Yibo (Hydrological Processes, 2008)
Seasonal changes over 2 years (2004-2006) in soil moisture content (0,,) of frozen alpine frost meadow soils of the Qinghai-Tibet plateau permafrost region under three different levels of vegetation cover were investigated. Vegetation cover and air temperature changes had significant effect (synergistic effect) on theta(v) and its distribution in the soil profile. During periods of soil freezing or thawing, the less the vegetation cover, the quicker the temperature drop or rise of soil water, and the shorter the duration of the soil water freeze-thaw response in the active soil layer. Under 30% and 65% vegetation cover the amplitude of variation in theta(v) during the freezing period was 20-26% greater than that under 93% cover, while during the thawing period, it was 1.5- to 40-5-fold greater. The freezing temperature of the Surface soil layer, (f)T(s), was 1.6 degrees C lower under 30% vegetation cover than under 93% vegetation cover. Changes in vegetation cover of the alpine frost meadow affected theta(v) and its distribution, as well as the relationship between theta(v) and soil temperature (T(s)). As vegetation cover decreased, soil water circulation in the active layer increased, and the response to temperature of the water distribution across the soil profile was heightened. The quantity of transitional soil phase water at different depths significantly increased as vegetation cover decreased. The influence of vegetation cover and soil temperature distribution led to a relatively dry soil layer in the middle of the profile (0.70-0.80 m) under high vegetation cover. Alpine meadow theta(v) and its pattern of distribution in the permafrost region were the result of the synergistic effect of air temperature and vegetation cover. Copyright (C) 2007 John Wiley & Soils, Ltd.